CHITOSAN-MEDIATED ORAL GENE THERAPY FOR HEMOPHILIA TREATMENT AND PROPHYLACTIC TOLERANCE - Dhadwar, Singh Sukhdeep (My University, 2011)
Hemophilia A and B are X-linked recessive bleeding disorders caused by the deficiency of coagulation factor VIII (FVIII) and Factor IX (FIX), respectively. Current treatment involves life-long protein replacement therapy which is invasive, expensive and inaccessible to the majority of hemophiliacs worldwide. Treatment is further compromised by the development of neutralizing antibodies. Thus, the development of an alternative treatment that is safer, cost effective and non-invasive that circumvents immune response induction is desirable.
To this end, a chitosan-mediated gene therapy strategy delivered orally was developed to provide clinically relevant plasma expression of FVIII or FIX. Hemophilia A mice that ingested chitosan nanoparticles containing FVIII DNA transiently expressed canine FVIII reaching >100 mU one day post treatment, together with partial phenotypic correction. Residual FVIII activity was detected for several days. Repeated administration of nanoparticles restored FVIII expression for 4 weeks and reduced clotting time in treated mice. Interestingly, inhibitors and non-neutralizing antibodies were not detectable throughout the experiment.
The immunomodulatory effects of chitosan-mediated oral gene delivery was investigated in naive hemophilia A mice and mice with pre-existing inhibitors. Administration of nanoparticles containing human FVIII DNA in naive mice suppressed systemic antibody responses and provided long-term tolerance to rhFVIII protein immunizations for at least 8 weeks. This tolerance was transferable to naive mice, suggesting development of regulatory T cells. In contrast, repeated oral nanoparticle administration was unable to suppress FVIII-specific antibody responses in hemophilia A mice with pre-existing inhibitors.
Treatment of hemophilia B is challenged by a 25-50 fold higher therapeutic threshold. Nevertheless, hemophilia B mice fed chitosan nanoparticles containing CpG-FIXi plasmid transiently expressed therapeutically relevant human FIX >14mU/mL plasma.
Chitosan nanoparticle formulation was optimized in vitro for improved transfection efficiency. Nanoparticles formulated at a chitosan:DNA charge ratio of >2:1 (N:P) provided DNA protection against proton and enzymatic degradation that mimic conditions of the stomach and intestine, respectively. The inclusion of 25 mM sodium acetate-acetic acid decreased transfection of HEK 293 cells 4-fold, while 50 mM sodium sulphate increased uptake by ~40%. Optimal transfection was achieved with chitosan chloride (CL 213) formulated at a charge ratio of 3:1 in 50 mM sodium sulphate.
These findings suggest chitosan nanoparticles can provide clinically relevant FVIII and FIX transgene expression, which is amenable to a one-tablet-a-day dosing strategy. Taken together, chitosan-mediate gene therapy delivered orally is proposed as a potential non-invasive alternative strategy for hemophilia treatment and without inducing neutralizing and non-neutralizing antibody production.
Keywords: gene delivery; hemophilia; gene therapy; Factor VIII; Factor IX; blood disorders; Biological Engineering; Biological Engineering